Sexual Education of Persons with Autistic Spectrum Disorders: Use of the Technique: ‘Social Stories - Stankova, Tanja; Trajkovski, Vladimir (Springer Nature, 2020)
The difficulty in the area of social skills for persons with Autism Spectrum Disorders (ASD) is particularly visible in the area of sexuality and intimate relationships. Therefore, it is important to create a curriculum including information about sexuality and to address the individual and specific needs of persons with ASD. For this purpose we designed a study using Social Stories for conducting sexuality education following the criteria of Carol Gray. The main goal of our study was to assess the effects of the use of Social Stories to implement sexuality education with three participants with ASD. The individual sessions lasted for 45 min and they continued for a period of 6 months. The participants were tested and their parents interviewed before starting and after finishing 6 months of sexual education, and this allowed us to assess knowledge and behavioral changes regarding sexuality. The most significant changes were determined through assessment of the following areas: the private and reproductive parts of the body; changes occurring during the period of puberty; distinguishing pleasant and unpleasant touch; sexual relations and contraception. Our conclusion after analyzing results were that a period of 6 months implementing sexuality education through Social Stories was sufficient to upgrade and expand knowledge, but definitely was insufficient for noticing visible behavioral changes.
Keywords: sexuality, sexuality education, persons with autism spectrum disorders, social stories, Republic of Macedonia